PERAN ORANGTUA DALAM MENUMBUHKAN IMAN ANAK SETELAH MENERIMA SAKRAMEN BAPTIS - Fajariyanto, Tri Chandra; Tambunan, Angel (Dharmas Education Journal (DE_Journal), 2024)
This research is to determine the role of parents in cultivating children's faith after receiving the sacrament of baptism at St. Peter's Station, Simpang Kuala, Medan. It can be concluded that the role of parents in Catholic families at St Peter's Simpang Kuala Medan Station is very important and varied, including education, guidance and assistance. Parents are responsible as the first educators who develop children's spirituality and teach them moral values and the five pillars of the church. They also act as guides in faith and behavior, as well as establishing rules and discipline within the family. In addition, as companions, parents engage in open communication, provide emotional support, and respect children's interests and potential. Parents also help children overcome life's challenges, shape character, and provide guidance in social interactions and decision making. Several opinions underscore the importance of supervision and being a good role model for children. In conclusion, parents have a very important role in forming character and ensuring healthy and quality growth in Catholic families.